Застосування апарату нечіткої логіки для аналізу контенту соціальних мереж - Гриценко, І. О. (ХНУРЕ, 2025)
This article is devoted to the development of a method for evaluating con tent in social networks using a fuzzy logic apparatus, which allows you to evalu ate not only the text of the comments themselves, but also the moods. The user will be able to obtain the results of public sentiment towards the publications that interest him.
Keywords: апарат нечіткої логіки; контент соціальних мереж